The Indigenous Birthing in an Urban Setting study: the IBUS study - Sophie Hickey; Yvette Roe; Yu Gao; Carmel Nelson; Adrian Carson; Jody Currie; Maree Reynolds; Kay Wilson; Sue Kruske; Renee Blackman; Megan Passey; Anton Clifford; et al. (BMC Pregnancy and Childbirth, 2018)
Abstract Background With persisting maternal and infant health disparities, new models of maternity care are needed to meet the needs of Aboriginal and Torres Strait Islander people in Australia. To date, there is limited evidence of successful and sustainable programs. Birthing on Country is a term used to describe an emerging evidence-based and community-led model of maternity care for Indigenous families; its impact requires evaluation. Methods Mixed-methods prospective birth cohort study comparing different models of care for women having Aboriginal and Torres Strait Islander babies at two major maternity hospitals in urban South East Queensland (2015–2019). Includes women’s surveys (approximately 20 weeks gestation, 36 weeks gestation, two and six months postnatal) and infant assessments (six months postnatal), clinical outcomes and cost comparison, and qualitative interviews with women and staff. Discussion This study aims to evaluate the feasibility, acceptability, sustainability, clinical and cost-effectiveness of a Birthing on Country model of care for Aboriginal and Torres Strait Islander families in an urban setting. If successful, findings will inform implementation of the model with similar communities. Trial registration Australian New Zealand Clinical Trial Registry #ACTRN12618001365257. Registered 14 August 2018 (retrospectively registered).